Shock shaping? Nebular spectroscopy of nova V906 Carinae. Issue 3 (22nd March 2023) - Harvey, É J; Aydi, E; Izzo, L; Morisset, C; Darnley, M J; Fitzgerald, K; Molaro, P; Murphy-Glaysher, F; Redman, M P; Shrestha, M
ABSTRACT: V906 Carinae was one of the best observed novae of recent times. It was a prolific dust producer and harboured shocks in the early evolving ejecta outflow. Here, we take a close look at the consequences of these early interactions through study of high-resolution Ultraviolet and Visual Echelle spectrograph spectroscopy of the nebular stage and extrapolate backwards to investigate how the final structure may have formed. A study of ejecta geometry and shaping history of the structure of the shell is undertaken following a spectral line $\rm {\small SHAPE}$ model fit. A search for spectral tracers of shocks in the nova ejecta is undertaken and an analysis of the ionized environment. Temperature, density, and abundance analyses of the evolving nova shell are presented.